Early allergy symptoms in infants aged 0-6 months on breast milk substitutes - Mulya Safri; Aulia Rahman Putra (Paediatrica Indonesiana, 2015)
Background Atopic diseases are common in children and a serious health problem worldwide. Atopic dermatitis, food allergies, asthma and allergic rhinitis, have been described as the natural progression of allergic diseases, also known as the â€œallergic marchâ€. Cowâ€™s milk protein is known to be a common trigger of food allergies and hypersensitivity reactions during infancy. Objective To give an overview of the breast milk substitutes (BMS) and incidence of early allergy onset (allergic march) in atopic infants aged 0-6 months. Methods This cross-sectional study included a total of 40 atopic infants collected by consecutive sampling. A questionnaire was used for interview that inquired information on the type of BMS used, initial allergy complaints, the age of the emergence of early allergic symptoms, and the breakdown for BMS type. Univariate analysis was carried out to describe their characteristics as frequency distributions and percentages of each variables. Results Atopic dermatitis and wheezing were more common in boys (62.5%). Atopic dermatitis was the most common initial symptom to occur in atopic infants (52.5%). Atopic dermatitis and wheezing occurred together in 27.5% subjects. Early allergy symptoms that first occurred at the age of 1 month were seen in 42.9% for atopic dermatitis category, 37.5% for wheezing category, and 63.6% for both symptoms category, respectively. Cowâ€™s milk was the most common type of BMS given to atopic infants in the first 6 months of life (47.5%). Conclusion Early symptoms of allergies, such as atopic dermatitis and wheezing, are more common in boys than girls. Atopic dermatitis is the most common early symptom to arise, but both symptoms occur at an early age, often during the first month of life.Â